Color Fundus Photography, Optical Coherence Tomography, and Fluorescein Angiography in Diagnosing Polypoidal Choroidal Vasculopathy - Voraporn Chaikitmongkol (2018)
© 2018 Elsevier Inc. Purpose: To determine sensitivity and specificity of polypoidal choroidal vasculopathy (PCV) diagnosis using color fundus photography (CFP), optical coherence tomography (OCT), and fundus fluorescein angiography (FFA) without indocyanine green angiography (ICGA). Design: Validity analysis. Methods: Treatment-naïve eyes with serous/serosanguinous maculopathy undergoing CFP, OCT, FFA, and ICGA imaging before treatment at a university hospital in Thailand (January 1, 2013 to June 30, 2015) were identified. Images of each subject were categorized into 4 sets (set A: CFP; set B: CFP+OCT; set C: CFP+FFA; set D: CFP+OCT+FFA). Six graders, 3 from Thailand (PCV endemic area) and 3 from the United States (nonendemic area), individually reviewed each set (without ICGA), and determined if the presumed diagnosis was PCV. In parallel, 2 other graders confirmed if each case had PCV or not using EVEREST criteria (including ICGA). Sensitivity and specificity of a PCV diagnosis with each set (without ICGA) were analyzed compared with diagnoses including ICGA. Results: Of 119 study eyes (113 subjects, 57% male, mean age ± SD 59.9 ± 13.8 years), definite PCV diagnosis was 40.3%. Sensitivity of sets A, B, C, D: 0.63 (95% confidence interval [CI]: 0.47–0.76), 0.83 (95% CI: 0.69–0.92), 0.54 (95% CI: 0.39–0.68), 0.67 (95% CI: 0.51–0.79); specificities: 0.93 (95% CI: 0.84–0.97), 0.83 (95% CI: 0.72–0.91), 0.97 (95% CI: 0.89–0.99), 0.92 (95% CI: 0.82–0.97); accuracies: 0.81 (95% CI: 0.73–0.88), 0.83 (95% CI: 0.76–0.90), 0.79 (95% CI: 0.73–0.87), 0.82 (95% CI: 0.74–0.88). Discrepancies between Thai and US graders existed through sets A, C, and D. Conclusions: These data suggest that without ICGA, fundus photography combined with OCT provides high sensitivity and high specificity to diagnose PCV; adding FFA does not improve accuracy.